Clinical Signs, Laboratory Diagnosis and Treatments Involved in Corona Viruses-19 - Israa Burhan Raoof; Zahraa Ahmed Okhti; Mayssaa E. Abdalah (College of Pharmacy / Mustansiriyah University, 2022)
Covid -19 is a viral disease play important role in danger pathogens for human, it is infecting on respiratory, hepatic, central nervous systems and gastrointestinal, in addition to that, the triggers included cytokine storm is inflammatory response to viral infection     Therefore, excessive enhance of immune cells lead to new of pro-inflammatory cytokines. COVID-19 interaction with the cardiovascular system on different levels, rising death percent in people underlying cardiovascular state provoking myocardial injury. Respiratory infection varying from   mild  cold to  the severe illness like  as Middle East Respiratory Syndrome and Severe Acute Respiratory Syndrome the most important coronavirus (COVID-19) complications, however individuals with asymptomatic disease were also suspected of possible infectious transmission, which further adds to the uncertainty of the dynamic of disease transmission in COVID-19 infections, Suppression of  angiotensin-converting enzyme (ACE2) expression by inflammatory cytokines accompanied by the decrease of estrogens and androgens  of the elderly, establish a negative correlation between   ACE2 expression and mortality in other cases may lead to infertility. Early detection by PCR has aided the identification of the pathogen at an early level.  Furthermore, the treatment includes the effectiveness of glucocorticoid drugs (dexamethasone), anti-malaria drug (hydroxychloroquine), azithromycin (antibacterial drug) and favipiravir are all drugs recommended in illness with Covid-19. Remdesivir suppression COVID-19 replication and decreases viral load, alleviates clinical signs and improves pulmonary injury, therefore Remdesivir drug has been used as a compassionate medicine for treating COVID-19 patients.